1981
DOI: 10.1002/1097-0142(19810315)47:6<1424::aid-cncr2820470630>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of survival to staging and grading of colorectal carcinoma: A prospective study of 503 cases

Abstract: A clinicopathologic staging method for colorectal carcinoma was applied prospectively to 503 patients treated by surgical resection over a period of 7 1/2 years. The method grouped separately those patients known to be incurable at the time of resection and allowed for an anatomically precise definition of the extent of tumor spread. Survival studies showed that prognosis did not significantly deteriorate with spread of tumor beyond the bowel wall unless there were demonstrable metastases, infiltration of a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
1
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(105 citation statements)
references
References 11 publications
3
100
1
1
Order By: Relevance
“…Poorly differentiated adenocarcinomas show invasive spreading histologically, and have a significantly poorer prognosis than well and moderately differentiated carcinomas (29). It has been reported that there was a significant correlation between the grade of histological differentiation and collagenolytic activity (30).…”
Section: Discussionmentioning
confidence: 99%
“…Poorly differentiated adenocarcinomas show invasive spreading histologically, and have a significantly poorer prognosis than well and moderately differentiated carcinomas (29). It has been reported that there was a significant correlation between the grade of histological differentiation and collagenolytic activity (30).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1971, clinical, operative, pathological and follow-up information on consecutive patients having a resection for rectal adenocarcinoma has been recorded prospectively in a computer database maintained at Concord Hospital 10 . Operations performed at Strathfield Private Hospital by members of the Concord colorectal unit have been included in the database since 1989.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to being the result of a subjective evaluation, histologic grade is known to be strongly correlated with stage in colorectal cancer (Newland et al, 1981), and its independent prognostic value is questionable. Nevertheless, Chapuis et al, (1985) (Jass et al, 1986).…”
Section: Methodsmentioning
confidence: 99%